A Model of Quality Assurance and Audit Quality Based on International Standards for Internal Auditing - Maher A. Al-Shmam; Ali Malallah Alsendy; A.Alazeez, Hosam Alden Riyadh (The International Journal of Accounting and Business Society, 2024)
Purpose — This study aimed to address the concept of internal audit quality and how to enhance and improve the quality of internal audit units in hospitals by identifying and designing a proposed new model based on the International Auditing Standard 1300 to ensure quality assurance and improve transparency and accountability. Design/methodology/approach — This study aims to achieve these objectives. Qualitative methods and semi-structured interviews using an inductive approach were adopted to cover the theoretical aspect of research and the deductive approach to develop a new model for a quality assurance and transparency program in hospitals in Iraq Mosul City. Findings —The findings of this internal audit division do not cover all hospital activities. In addition, it is not possible to apply standardized audit programs to the various units. Rather, the type of activities carried out by these units should be considered, whether service, economic, commercial, or agricultural. Thus, many factors improve the quality of internal auditing related to work procedures in the unit. Among the most important recommendations is implementing a quality assurance and transparency program in these hospitals to raise the quality of internal auditing and carry out its activities efficiently and effectively. Practical implications —This proposal can serve as a guide for later use by those authorities as they evaluate and determine the strength of the internal audit of any establishment, company, or governmental institution. Therefore, hospitals must apply the paragraphs that are not included in the program, and there should be greater interest in the paragraphs that are applied in a weak way to reach real integration of the quality assurance and improvement program, which enhances the quality of internal auditing on all hospital activities. Originality/value —This paper describes a quality assurance and transparency program in these hospitals to improve internal audits and efficiency.